3, 4-Methylenedioxymethamphetamine (MDMA, Ecstasy) Intoxication in a Young Adult with Giant Coronary Aneurysms from Kawasaki Disease. Issue 3 (September 2018) - Eigsti, Renee; Firchau, Dennis J.; Nashelsky, Marcus B.
Kawasaki disease is an acute vasculitis of unknown etiology that usually occurs in children less than five years old. Coronary artery aneurysm due to arteritis is the most common cardiac complication. Chronic aneurysms are associated with an increased risk of developing luminal thrombosis and ischemic myocardial injury. We present a case of an 18-year-old male with a history of Kawasaki disease complicated by chronic giant aneurysms of the right and left coronary arteries. Serial echocardiographic studies and treadmill electrocardiogram stress tests as recent as 1.5 years before death revealed excellent cardiac function by clinical criteria. The decedent sustained a witnessed collapse after ingesting 3, 4-methylenedioxymethamphetamine (MDMA) and ethanol. He was pronounced dead in the emergency department after unsuccessful resuscitative efforts. Autopsy revealed large aneurysms of the three main epicardial coronary arteries with extensive foci of severe stenosis by intimal fibrosis and organizing thrombus. Microscopic examination revealed multifocal severe myocyte hypertrophy. There were remote microinfarcts in the anterior and posterior aspects of the left ventricle and a recent, healing microinfarct in the posterior aspect of the left ventricle. Toxicology examination of postmortem femoral blood revealed MDMA, ethanol, and amiodarone. This case illustrates the residual, lasting effects of cardiac disease due to Kawasaki disease and a potential complication in the setting of use of an illicit stimulant, MDMA, an amphetamine derivative that produces sympathetic activation and cardiovascular effects including tachycardia, vasoconstriction, dysrhythmias, and coronary artery spasm. Kawasaki disease-related abnormalities of the heart likely resulted in a lower threshold for developing a fatal cardiac dysrhythmia under the circumstance of stimulant use.